1980
DOI: 10.2307/279293
|View full text |Cite
|
Sign up to set email alerts
|

Gallinazo Maize from the Chicama Valley, Peru

Abstract: A large sample of Gallinazo cobs from Huaca Prieta is classified using a set of five variables. Some types of Gallinazo maize recovered there seem to have been new to the Peruvian North Coast; some types of the preceding Salinar phase are not known from this site. Further changes occur in the Chicama-Viru area when Moche influence appears. In several ways Gallinazo maize seems more related to maize occurring today further north and east than to modern highland or coastal maize to the southeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Here, excavations reported by Bird and Hyslop (53) showed that earlier deposits were overlain by a Gallinazo occupation in Test Pit HP1, which included a facility with a concentration of clay-lined pits and a large jar (figures 13-14 of ref. 53), associated with 571 maize cobs whose kernels had been removed (54). The HP1 facility shows similarities to facilities documented ethnographically and archaeologically for the production of maize beer or chicha (55)(56)(57).…”
Section: Perumentioning
confidence: 87%
“…Here, excavations reported by Bird and Hyslop (53) showed that earlier deposits were overlain by a Gallinazo occupation in Test Pit HP1, which included a facility with a concentration of clay-lined pits and a large jar (figures 13-14 of ref. 53), associated with 571 maize cobs whose kernels had been removed (54). The HP1 facility shows similarities to facilities documented ethnographically and archaeologically for the production of maize beer or chicha (55)(56)(57).…”
Section: Perumentioning
confidence: 87%
“…As discussed above, the morphology of maize is the product of genetic, environmental, and other developmental factors (Adams et al, 1999;Benz, 1994b;Goodman and Paterniani, 1969;King, 1994;Sánchez González et al, 1993;Turkon, 2006). Indeed, researchers have studied maize at the morphological level to ascertain the possible races of maize present in archaeobotanical assemblages as well as the production of maize in distinctive ecological contexts (Benz, 1994b;Benz and Iltis, 1990;Bird, 1994;Bird and Bird, 1980;Doebley and Bohrer, 1983;Johannessen et al, 1990;King, 1994;Miksicek et al, 1981;Huckell, 2006;Turkon, 2006;Villa Kamel et al, 2003).…”
Section: Maize Samplesmentioning
confidence: 95%
“…Indeed, scholars have conducted such analyses to determine the specific varieties present in archaeobotanical assemblages (e.g., Benz, 1994a;Bird and Bird, 1980;McClung de Tapia, 1977;Miksicek et al, 1981;Morehart, 2002;Villa Kamel et al, 2003). Yet, carbonization of the archaeobotanical remains usually causes not only their shrinkage but can distort some features.…”
Section: Limitations and Avenues For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…-Espécies sobre as quais não há informação para período e sítio. O número de X e * simboliza a proporção relativa da planta no registro arqueobotânico do período (Bird & Bird, 1980;Bird et al, 1985;Pozorski & Pozorski, 1993;Billman, 1996, Elera et al, 1992Elera, 1993Elera, , 1998Cárdenas, 1977;Gonzáles, 2007;Piperno & Dillehay, 2008 …”
unclassified